Proses Manajemen Resiko Pada Usaha Kios Pelita Harapan - Cicilia Ayu Wulandari Nuwa; Carol Fabianus; Stefrian Claudio; Albertus Karles; Yeremias Gewar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Micro and small businesses such as grocery kiosks face various operational risks that can threaten business sustainability; however, most business owners have not yet implemented systematic risk management practices. This study aims to analyze the risk management process at Kios Pelita Harapan, a small business established in September 2023 in Maumere, using a qualitative approach through direct interviews with the business owner. The findings reveal that the risk management process at this kiosk encompasses four stages: risk identification, risk analysis and assessment, risk evaluation and prioritization, and implementation and monitoring. The primary risks identified include stockouts of fast-moving goods, product damage due to short expiry periods, fire hazards, power outages, and theft. The owner addresses these risks through daily stock checking, inventory recording, monitoring customer purchasing patterns, and coordinating with suppliers during emergencies. The application of a simple yet structured risk management approach has been proven effective in stabilizing revenue and maintaining customer trust. This study provides practical implications for kiosk business owners in implementing effective risk management despite limited resources.